2018
DOI: 10.31234/osf.io/f7tvd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambivalence, the Person and the Attitude Object: Individual Differences in the Experience of Ambivalence

Abstract: Ambivalence, that is holding positive and negative evaluations about a single topic, has traditionally been studied in relation to specific attitude objects. However, prior findings suggest that some individuals may be more ambivalent than others, regardless of the attitude object. To investigate this possibility, we conducted a registered secondary analysis of two existing datasets. In both datasets, individuals (ns = 41; 111) rated multiple stimuli (DS1=29; DS2=61) drawn from widely-used normed sets (IAPS; A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Interestingly, we found that individuals who were more ambivalent across various brands also showed more change in their attitudes over time. This pattern is consistent with ambivalence as a sign of weaker attitudes but is intriguing because it occurs at the level of the individual (Britt et al, 2011; Simons, Schneider, & Sanchez-Burks, 2019). Because many studies in the attitude-strength literature tend to measure one attitude at a time, they confound attitude attributes that are specific to a given target with individual propensities to hold attitudes with those attributes.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, we found that individuals who were more ambivalent across various brands also showed more change in their attitudes over time. This pattern is consistent with ambivalence as a sign of weaker attitudes but is intriguing because it occurs at the level of the individual (Britt et al, 2011; Simons, Schneider, & Sanchez-Burks, 2019). Because many studies in the attitude-strength literature tend to measure one attitude at a time, they confound attitude attributes that are specific to a given target with individual propensities to hold attitudes with those attributes.…”
Section: Discussionsupporting
confidence: 76%
“…More recently, these findings were extended by work using multi-level modeling approaches, a larger dataset, and a wider range of attitude objects. In this study, interindividual differences accounted for 16%-28% of the variance in state ambivalence over all included attitude objects (Simons et al, 2020). These findings demonstrate that differences in ambivalence reflect a general tendency to be more ambivalent over situations and attitude objects.…”
Section: Introductionsupporting
confidence: 52%
“…So far, this work has focused on state ambivalence, an experience that emerges in response to a specific stimulus. However, there is evidence indications that there are also stable individual differences in ambivalence (Simons et al, 2020;. That is, some people are chronically more ambivalent than others.…”
Section: Introductionmentioning
confidence: 99%
“…So far, this work has focused on state ambivalence, an experience that emerges in response to a specific stimulus. However, there is evidence that there are also stable individual differences in ambivalence (Simons et al ., 2020; Thompson & Zanna, 1995). That is, some people are chronically more ambivalent than others.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, these findings were extended by work using multi‐level modelling approaches, a larger data set, and a wider range of attitude objects. In this study, interindividual differences accounted for 16%–28% of the variance in state ambivalence over all included attitude objects (Simons et al ., 2020). These findings demonstrate that differences in ambivalence reflect a general tendency to be more ambivalent over situations and attitude objects.…”
Section: Introductionmentioning
confidence: 99%